1999
DOI: 10.1088/0022-3727/32/10/304
|View full text |Cite
|
Sign up to set email alerts
|

Particle capture in axial magnetic filters with power law flow model

Abstract: A theory of capture of magnetic particle carried by laminar flow of viscous non-Newtonian (power law) fluid in axially ordered filters is presented. The velocity profile of the fluid flow is determined by the Kuwabara-Happel cell model. For the trajectory of the particle, the capture area and the filter performance simple analytical expressions are obtained. These expressions are valid for particle capture processes from both Newtonian and non-Newtonian fluids. For this reason the obtained theoretical results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…The motion equations of the magnetic particles in parallel stream type HGMS with circular cross-section matrices were investigated in previous studies (Briss et al, 1976;Uchiyama et al, 1976;Gerber, 1978;Abbasov et al, 1999) and the expressions in cylindrical coordinate system are shown in the following equations: 193 Parallel stream HGMS where r d ¼ r/d, V m ¼ 2κM s H 0 R 2 /9ηd, d is the radius of the circular matrices, r is the distance between the particle and the matrix axis. The particle capture cross-section of the elliptic matrices and the circular matrices then can be calculated with Equations (19)-(21) and Equations (22)-(24), respectively.…”
Section: Comparisons Of the Particle Capture Cross-sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motion equations of the magnetic particles in parallel stream type HGMS with circular cross-section matrices were investigated in previous studies (Briss et al, 1976;Uchiyama et al, 1976;Gerber, 1978;Abbasov et al, 1999) and the expressions in cylindrical coordinate system are shown in the following equations: 193 Parallel stream HGMS where r d ¼ r/d, V m ¼ 2κM s H 0 R 2 /9ηd, d is the radius of the circular matrices, r is the distance between the particle and the matrix axis. The particle capture cross-section of the elliptic matrices and the circular matrices then can be calculated with Equations (19)-(21) and Equations (22)-(24), respectively.…”
Section: Comparisons Of the Particle Capture Cross-sectionmentioning
confidence: 99%
“…To compare the particle capture cross-section of the elliptic matrices and the circular matrices, the motion equations of the magnetic particles around the two kinds of matrices should be known. The motion equations of the magnetic particles in parallel stream type HGMS with circular cross-section matrices were investigated in previous studies (Briss et al, 1976;Uchiyama et al, 1976;Gerber, 1978;Abbasov et al, 1999) and the expressions in cylindrical coordinate system are shown in the following equations:…”
Section: Comparisons Of the Particle Capture Cross-sectionmentioning
confidence: 99%
“…The mechanical recovery fraction was considered as (16) Therefore, the equation below could be written for the total fractional recovery of paramagnetic particles (17) In fact, because of the very irregular packing of the steel wool fibers in the filter, there is a significant fraction of the particles to be mechanically trapped. According to these results as well as to the work done by Uchima [20], in the case of a random packed wool matrix, not only magnetic particles but also nonmagnetic particles will be mechanically trapped at the portion perpendicular to the slurry flow, which is unfavorable not only for the separation of magnetic particles from nonmagnetic ones but also for the flushing of the filter.…”
Section: Review Of the Mathematical Modeling Of The Process A Cmentioning
confidence: 99%
“…HGMS performansı ise parçacığın tutulma yarıçapına göre belirlenir [4,14]. Bu teori baz alınarak HGMS'lerin taşıyıcı ortamın ideal [13], newtonian-aminer [3,14], reolojik [15] akış rejimlerinde performans karakteristikleri incelenmiştir. Son yıllarda ise mtris elemanları elipsoid kesitli HGMS'lerin teori ve pratiği literatürde geniş olarak incelenmektedir [16][17][18][19][20].…”
Section: Gi̇ri̇ş (Introduction)unclassified